Conceptual Framework for Utilizing Augmented Reality/Virtual Reality in Creating a Smart Education Ecosystem in Construction Management Learning - Hansen, Seng (Semarak International Journal of STEM Education, 2025)
Along with the development of information technology, the metaverse appears to facilitate the interaction of its users in the digital space. Various new technologies, such as Building Information Modeling (BIM), augmented reality/virtual reality (AR/VR), and digital twins, have begun to be applied in the construction industry. However, the use of these technologies has not been widely applied in education, such as in the construction management learning process in universities. This paper aims to explore the potential use of AR/VR technology in learning various courses related to construction management. It employed a qualitative approach through a focused literature review. The findings are eleven potential applications of AR/VR in construction management education, including utilization for construction occupational health and safety, construction method, and construction surveying courses. This is important considering that construction management courses need full understanding of the construction project environment, both in actual site visits and through digital representations. This paper also contributes by developing a conceptual framework for the use of AR/VR technology to create a smart education ecosystem, especially in the field of construction management. It serves as a starting point for higher education institutions to begin integrating immersive technology into a more adaptive, collaborative, and data-driven learning process.